The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/agg2.20311
|View full text |Cite
|
Sign up to set email alerts
|

Residue decomposition dynamics in mixed ratios of two warm‐season cover crops

Abstract: Cover crop residue management has gained attention over the past few decades due to the potential of cover crop residues to provide soil cover and nutrient availability for subsequent crops. Nutrients released from cover crop residues depend on the nutrient composition of plant tissue and ensuing rates of mineralization. To evaluate the rate of carbon (C) and nitrogen (N) mineralization from cover crops, a field decomposition experiment was conducted in a humid subtropical agricultural field. Residues of two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Many studies have reported that in crop rotation, below-ground rhizodeposits and root addition are the key factors of carbon accumulation in the soil, accounting for up to 75% of soil organic matter (Jones et al, 2009;Ghani et al, 2022d). Different types of crop stalks, twigs, dead roots as well as fallen leaves are important sources of nutrients Aschi et al (2017), while leafy vegetables used as crop rotation can scavenge nutrients from the soil, store it in their residues and return it to the soil for the next crop through root decomposition and improved SOM (Dorissant et al, 2022;Ghani et al, 2022b). Kong and Six (2012) reported that living cover crops significantly improved soil organic matter compared to bare fallow due to the rhizodeposition of low molecular carbon into the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that in crop rotation, below-ground rhizodeposits and root addition are the key factors of carbon accumulation in the soil, accounting for up to 75% of soil organic matter (Jones et al, 2009;Ghani et al, 2022d). Different types of crop stalks, twigs, dead roots as well as fallen leaves are important sources of nutrients Aschi et al (2017), while leafy vegetables used as crop rotation can scavenge nutrients from the soil, store it in their residues and return it to the soil for the next crop through root decomposition and improved SOM (Dorissant et al, 2022;Ghani et al, 2022b). Kong and Six (2012) reported that living cover crops significantly improved soil organic matter compared to bare fallow due to the rhizodeposition of low molecular carbon into the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The ground samples were analysed for N (Bremner and Mulvaney 1982),C and P (Chapman and Pratt 1961). Residue from each bag was also prepared and burned to identify soil mineral contaminants in a furnace at 550C for 4 h. Litterbag content is reported on an ash-free dry weight basis (Dorissant et al 2022).…”
Section: Litter Bag Experimentsmentioning
confidence: 99%